1993
DOI: 10.1152/ajpgi.1993.265.6.g1141
|View full text |Cite
|
Sign up to set email alerts
|

Murine intestinal disaccharidases: identification of structural variants of sucrase-isomaltase complex

Abstract: This study was directed to determine the extent of variability in structure or expression of intestinal disaccharidase [gamma-glucoamylase (gamma-GA), sucrase-isomaltase (SI), and lactase] between different strains of mice. Reduced levels of sucrase activity (approximately 20 U/g of protein) were observed in three strains of mice belonging to the CBA/Ca lineage. Four other strains of mice analyzed exhibited higher levels of sucrase activity (approximately 50 U/g of protein). Decreased levels of sucrase in CBA/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…One unit (U) of enzyme activity was defined as the activity that cleaves 1 μmol of maltose per minute. The mixtures were incubated for 1 h at 37 °C, and then TGO (180 μL) was added and incubated for an additional 45 min . Absorbance was read at 450 nm in the microplate reader.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One unit (U) of enzyme activity was defined as the activity that cleaves 1 μmol of maltose per minute. The mixtures were incubated for 1 h at 37 °C, and then TGO (180 μL) was added and incubated for an additional 45 min . Absorbance was read at 450 nm in the microplate reader.…”
Section: Methodsmentioning
confidence: 99%
“…Enzyme and Inhibition Assays. Glucose release was measured according to the tris glucose oxidase (TGO) method 36 modified for microplate wells. Maltose solution (10 μL) at final concentrations ranging from 2.1 to 16.7 mM (approximately 1−8 times the K m for maltose of Ct subunits and 0.3−3 times the K m for maltose of Nt subunits) was mixed with 10 μL of the enzyme solution containing 0.2 mU of activity for Ct-MGAM, Ct-SI, and Nt-MGAM and 0.1 mU of activity for Nt-SI.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…This result also strongly indicated that the structure of the intestinal BBM and development of intestinal BBM enzymes in Wistar rats were markedly influenced by age during the postnatal period. Key words: age, ALP, disaccharidase, γ-GT, microvilli the organs [4,13,23,31]. Among various organs, the epithelial cells lining the lumen of the gut are the first membrane barrier between the outside environment and the inside circulator in response to external and internal stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Although co-varying to some extent with dietary carbohydrate levels, expression of lactase and sucrase-isomaltase is not primarily regulated by the presence of their substrates, but appears to be genetically determined [13,14]. Aspects of the temporal and spatial patterns of lactase and sucrase-isomaltase gene expression in vivo in several species (rat, rabbit, pig, human and mouse) have been described [15][16][17][18][19][20][21][22][23][24]. However, quantitative interpretation of these studies is hampered because tissue homogenates were used and consequently many cell types were studied simultaneously, thereby obscuring the contribution of enterocytes to the levels of disaccharidase mRNA, protein and activity.…”
Section: Introductionmentioning
confidence: 99%